From the editors - Esterhuyse, Abel; Liebenberg, Ian (Scientia Militaria - South African Journal of Military Studies, 2012)
Military science, like conflict, war and warfare from which the discipline derived its existence, is a broad and complex field of study. The focus of Scientia Militaria, the South African Journal of Military Studies, has always been driven by two key considerations. Firstly, an interdisciplinary approach to the study of all things military and, secondly, an understanding that, irrespective of how widely the study of military affairs, the idea of warfighting and the need to be effective in the use of military forces in the provision of security, remains at the heart of military sciences. This edition of the journal is a typical reflection of this focus.